Manusia Satu Dimensi Menurut Herbert Marcuse - Bukan, Paulus Kus (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2024)
This article aims to explain on the concept of one-dimensional man of Herbert Marcuse. One-dimensional man is a term used by Herbert Marcuse to criticize modern society that is too submissive under the principle of technology. In his idea, Marcuse considers that technology worked on by capitalists has turned into the most repressive ideology that makes humans in modern society passive and uncritical. Modern technology is also transformed into a tool of social control and then takes over human life. Its main goal is to paralyze critical reasoning so that humans do not negate the system. Consequently, humans no longer move from their authenticity but move according to what is shown through a burst of symbols produced by technology. Humans feel themselves free and happy but without realizing it, they are being manipulated, oppressed and enslaved by the technological rationality system. This system of technological rationality then gave birth to one dimensional man. One dimensional man are humans who only move in one direction, which is none other than to perpetuate the system implemented by the capitalists.